2014
DOI: 10.1007/s10615-014-0491-4
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Bereavement and Mindfulness: A Preliminary Study of Mental Health Outcomes Using the ATTEND Model

Abstract: This article presents a quasi-experimental study of a mindfulness-based intervention for traumatically bereaved individuals using a single group with pre-test and post-test design. The intervention consists of the ATTEND model, which is comprised of the following elements practiced by the clinician: attunement, trust, therapeutic touch, egalitarianism, nuance, and death education. The study is based on the charts of 42 clients seeking grief counseling at a mental health agency viewed retrospectively. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
(56 reference statements)
2
29
0
Order By: Relevance
“…From the perspective of the broaden-and-build theory (Fredrickson, 1998(Fredrickson, , 2001, decentering awareness may broaden one's attention, which in turn may lead to more flexible thinking styles and positive emotions (e.g., compassion; Garland et al, 2010). Results from pilot studies showed the potential effectiveness of mindfulness-based treatment for reducing depression and PTSD levels among bereaved people (O'Connor et al, 2014;Thieleman et al, 2014). Future studies are needed to further explore the potential beneficial effect of this type of grief treatment.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of the broaden-and-build theory (Fredrickson, 1998(Fredrickson, , 2001, decentering awareness may broaden one's attention, which in turn may lead to more flexible thinking styles and positive emotions (e.g., compassion; Garland et al, 2010). Results from pilot studies showed the potential effectiveness of mindfulness-based treatment for reducing depression and PTSD levels among bereaved people (O'Connor et al, 2014;Thieleman et al, 2014). Future studies are needed to further explore the potential beneficial effect of this type of grief treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other third-wave cognitive behavioural treatments, such as compassion-focused therapy and acceptance and commitment therapy, are increasingly being used to target these phenomena (Beaumont & Hollins Martin, 2015; Dindo, Van Liew, & Arch, 2017). The first results of small trials among bereaved persons showed that mindfulness-based interventions might be effective in reducing symptoms of depression (O’Connor et al, 2014; Thieleman et al, 2014), anxiety, and PTS (Thieleman et al, 2014). Although non-significant reductions were found in PG and PTS levels in O’Connor et al’s (2014) study and some participants in Thieleman et al’s study (2014) reported increased symptomatology following the mindfulness-based treatment, it may be valuable to further study the potential effectiveness of these interventions, because the current treatment-of-choice, cognitive behavioural therapy, results in clinically relevant change in PG levels in at most 50% of people with PG (Doering & Eisma, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In general, mindfulness refers to present moment awareness to any inner experiences, whereas self-compassion is targeted at embracing one’s own suffering (Neff & Dahm, 2015). Preliminary findings of small clinical trials among bereaved people indicate that mindfulness-based approaches might be equally beneficial for targeting psychopathology levels in bereaved people as in non-bereaved people who suffer from similar complaints such as depression (O’Connor, Piet, & Hougaard, 2014; Thieleman, Cacciatore, & Hill, 2014). However, the link between self-compassion and psychopathology after bereavement, including PG symptoms, has, to the best of our knowledge, never been studied.…”
mentioning
confidence: 99%
“…Within the context of bereavement, the concept of acceptance has been integral to clinical mindfulness interventions that have been developed, such as based on the ATTEND (attunement, trust, touch, egalitarianism, nuance, and death education) framework [ 81 ]. However, evaluations of these interventions have thus far been limited [ 126 ].…”
Section: Coping and Appraisalmentioning
confidence: 99%